2019
DOI: 10.1002/smll.201804968
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Specific Detection of Exosomal miRNAs for Accurate Diagnosis of Breast Cancer Using a Surface‐Enhanced Raman Scattering Sensor Based on Plasmonic Head‐Flocked Gold Nanopillars

Abstract: MicroRNAs in exosomes (exosomal miRNAs) have attracted increased attention as cancer biomarkers for early diagnosis and prognosis owing to their stability in body fluids. Since strong association exists between exosomal miRNA expression levels and breast cancer, the development of effective methods that can monitor exosomal miRNA expression both over broad concentration ranges and in ultralow amounts is critical. Here, a surface‐enhanced Raman scattering (SERS)‐based sensing platform is developed for the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 68 publications
2
105
0
1
Order By: Relevance
“…Many studies have shown that microRNAs were associated with pathogenesis in different forms of tumors (45)(46)(47)(48). Therefore, further comparison and analysis of the microRNA expression profiles among TNBC patients' tumor tissues and their control tissues adjacent to cancer, or other types of breast cancer tumor specimens and normal control breast tissues were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that microRNAs were associated with pathogenesis in different forms of tumors (45)(46)(47)(48). Therefore, further comparison and analysis of the microRNA expression profiles among TNBC patients' tumor tissues and their control tissues adjacent to cancer, or other types of breast cancer tumor specimens and normal control breast tissues were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This powerful strategy can be applied to the detection from smaller biomarkers until tissue exemplars. For example, Lee et al (Figure 4A), developed a SERS-based sensor for quantitative detection of exosomal miRNA in serum samples of breast cancer patients [39]. Hybrid structure consists in a head-flocked gold nanopillar substrate functionalized with a specific locked nucleic acid (LNA) probes for capturing miR-21, miR-222, and miR-200c added in known concentrations to human serum.…”
Section: Encoded-sersmentioning
confidence: 99%
“…Finally, the novelty provided by Lee et al [39] consists in a dispositive able to detect two kinds of biomarkers simultaneously: CTCs and DNA. They developed a dual-function nanodevice for capturing nasopharyngeal CTCs and detecting Epstein-Barr virus (EBV) DNA from plasma samples with a LOD of 10 −13 M [37].…”
Section: Encoded-sersmentioning
confidence: 99%
“…Surface enhanced Raman scattering (SERS) is an extension of the spectroscopic method developed on the basis of Raman spectra and metal nanoparticles (AuNPs or AgNPs) (Lee et al, 2019;Yu B.R. et al, 2019).…”
Section: Sers Aptasensorsmentioning
confidence: 99%